The effect of implementing the search, solve, create and share (sscs) learning model using bar modelling on improving students' mathematical problem-solving abilities - Askalani, Ibnu; Izzati, Nurma; Akbar, Reza (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2026)
The capacity for mathematical problem-solving constitutes a vital proficiency in mathematics education.Nevertheless, the proficiency level of Indonesian students in this domain remains suboptimal. Thisresearch endeavors to explore students’ perceptions of the integration of the Search, Solve, Create, andShare (SSCS) pedagogical model, augmented with bar modelling, and to evaluate its efficacy inadvancing their mathematical problem-solving competencies. Employing a quasi-experimentalframework with a non-equivalent control group design, the study utilized instruments such as a studentresponse questionnaire and a diagnostic assessment aligned with Polya’s problem-solving indicators.Findings reveal that student responses to the instructional approach fall under the “very good”classification, yielding an average score of 80.57%. Furthermore, the experimental group demonstrateda substantial enhancement in problem-solving capability, reflected in a normalized gain (N-Gain) of 0.79,while the control group exhibited a markedly lower N-Gain of 0.20. Results from the independentsample t-test produced a significance level (Sig. 2-tailed) of 0.000 < 0.05, indicating a statisticallysignificant divergence between the two cohorts. Consequently, it can be inferred that the SSCS model,when combined with bar modelling, serves as an effective and engaging instructional paradigm forbolstering students’ mathematical problem-solving aptitude.